The Role of Cyberwar in Modern Warfare - Nehaluddin AHMAD; Ahmad MASUM; Azeem KHAN; Faizah RAHIM (Communications of International Proceedings, 2025)
Warfare in the twenty-first century has increasingly shifted from traditional battlefields to digital and informational spaces, with cyberwarfare becoming a central tool in both military strategy and diplomacy. Despite growing attention to cyber operations, there is limited research on how these tactics blur the line between peace and war and challenge established norms of sovereignty and international humanitarian law. The recent India-Pakistan confrontation illustrates how modern militaries now integrate cyber capabilities with conventional technologies, creating strategic, operational, legal, and ethical challenges that remain underexplored. This article examines news reports, open-source materials, official documents, and articles of contemporary cyber operations. Close reading of these sources reveals patterns that are not immediately visible, including a growing focus on controlling information rather than territory. The transformation complicates deterrence, raises normative and legal uncertainties, and presents difficult questions of accountability in cyberspace. It stresses that states need to build robust cyber policies, establish clear legal frameworks, and enhance interagency coordination to respond effectively to emerging threats. Drawing on these insights, the article identifies how cyber warfare is changing conflict behaviour, undermining the force of international law and reshaping security policy in today’s digital and information-driven era. These findings highlight the importance for policymakers, legal and security professionals to not only consider changing levels of power or military systems imposed within military warfare, but furthermore to confront developments in this domain and battlefield environment of cyber-enabled warfare.
Keywords: Cyberwarfare; Modern Warfare; Digital Sovereignty; International Humanitarian Law; Information Security